Rare mutations of ADAM17 from TOFs induce hypertrophy in human embryonic stem cell-derived cardiomyocytes via HB-EGF signaling. (22nd January 2019) - Xie, Yifang; Ma, Anyun; Wang, Boshi; Peng, Rui; Jing, Yingchun; Wang, Deqian; Finnell, Richard H.; Qiao, Bin; Wang, Yongming; Wang, Hongyan; Zheng, Yufang
Abstract : Tetralogy of Fallot (TOF) is the most common cyanotic form of congenital heart defects (CHDs). The right ventricular hypertrophy is associated with the survival rate of patients with repaired TOF. However, very little is known concerning its genetic etiology. Based on mouse model studies, a disintergrin and metalloprotease 10/17 (ADAM10 and ADAM17) are the key enzymes for the NOTCH and ErbB pathways, which are critical pathways for heart development. Mutations in these two genes have not been previously reported in human TOF patients. In this study, we sequenced ADAM10 and ADAM17 in a Han Chinese CHD cohort comprised of 80 TOF patients, 286 other CHD patients, and 480 matched healthy controls. Three missense variants of ADAM17 were only identified in 80 TOF patients, two of which (Y42D and L659P) are novel and not found in the Exome Aggregation Consortium (ExAC) database. Point mutation knock-in (KI) and ADAM17 knock-out (KO) human embryonic stem cells (hESCs) were generated by CRISPR/Cas9 and programmed to differentiate into cardiomyocytes (CMs). Y42D or L659P KI cells or complete KO cells all developed hypertrophy with disorganized sarcomeres. RNA-seq results showed that phosphatidylinositide 3-kinases/protein kinase B (PI3K/Akt), which is downstream of epidermal growth factor receptor (EGFR) signaling, was affected in both ADAM17 KO and KI hESC-CMs. In vitro experiments showed that these two mutations are loss-of-function mutations in shedding heparin-binding EGF-like growth factor (HB-EGF) but not NOTCH signaling. Our results revealed that CM hypertrophy in TOF could be the result of mutations in ADAM17 which affects HB-EGF/ErbB signaling.